The Effect of Self-Actualization Needs, Appreciation and Social Needs on Employee Work Achievement at PT. Nusantara III Plantation Rantauprapat - Siafaruddin Munte (Cita konsultindo, 2025)
The influence of self-actualization needs, appreciation and social needs in PT. Perkebunan Nusantara III Rantauprapat plantation by using a quantitative research method with data analysis techniques using the SPPS for windows application with questionnaire data distributed by 57 people at the university, obtained from the results of the study it was seen that the independent variables, namely Self-Actualization, Appreciation and Social Needs, had a ttable > ttable value of (0.776 > 0.679); (2,177 > 0.679) ; ( 1.791 > 0.679) with probability values of 0.441, 0.34, 0.79 > 0.05, then the Ha hypothesis is rejected which means that partially the variables Self-Actualization, Reward and Social Needs have a positive and significant effect on Work Performance.